(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article describes the architectural planning principles, options and methods of designing art schools. The approaches to the formation of an architectural environment that promotes the development of students’ creative potential are considered, including the principles of flexible spaces, integration of digital technologies and sustainable construction. Particular attention is paid to the interaction of the architectural appearance of buildings with the urban context and the need for multifunctionality of educational and cultural and leisure areas. Based on foreign experience, key trends are identified that shape the modern design of art education institutions.